2011
DOI: 10.1143/jjap.50.082302
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Organic Photovoltaic Cells with Solution-Processed Zinc Oxide as Electron Collecting Layer

Abstract: In this work, inverted polymer:fullerene organic photovoltaic (OPV) cells with solution-processed zinc oxide (ZnO) as the electron collecting layer are investigated. ZnO films are prepared simply by the spin-casting of a zinc acetate dehydrate precursor solution, followed by sintering under ambient conditions. The performance of the fabricated inverted OPV cells shows a clear dependence on precursor concentration and sintering conditions. With the ZnO film derived from a sol-gel concentration of 0.1 M and sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 24 publications
(78 reference statements)
3
34
0
Order By: Relevance
“…Effi ciently and economically harnessing the solar energy has always been an interesting topic for human beings to generate renewable energy. [1][2][3][4][5][6][7] Very recently, the high-effi cient and low-cost perovskite hybrid solar cells (pero-HSCs) have shown great potentials to be the fourth-generation photovoltaics, breaking the deadlock previously dominated by organic and inorganic photovoltaics. [8][9][10][11][12] Because of their ideal physical properties for photovoltaics such as broad absorption coverage with high extinction coeffi cients, [ 13 ] long charge carrier diffusion length, [ 14 ] and good electrical transport properties, [ 15 ] the methylammonium lead halide…”
Section: Introductionmentioning
confidence: 99%
“…Effi ciently and economically harnessing the solar energy has always been an interesting topic for human beings to generate renewable energy. [1][2][3][4][5][6][7] Very recently, the high-effi cient and low-cost perovskite hybrid solar cells (pero-HSCs) have shown great potentials to be the fourth-generation photovoltaics, breaking the deadlock previously dominated by organic and inorganic photovoltaics. [8][9][10][11][12] Because of their ideal physical properties for photovoltaics such as broad absorption coverage with high extinction coeffi cients, [ 13 ] long charge carrier diffusion length, [ 14 ] and good electrical transport properties, [ 15 ] the methylammonium lead halide…”
Section: Introductionmentioning
confidence: 99%
“…RT‐deposited ZnO showed a higher PCE of 5.83%, 6.9%, and 6.8% at 2, 5, and 8 mTorr deposition pressure, respectively. However, the previous reports suggested that the annealed ZnO films at temperatures as high as 500 °C showed improved PCE compared to the as‐deposited ones . Hence, the physical origin of enhanced PCE with RT‐deposited ZnO needs to be explored.…”
Section: Pbdttpd:pc71bm Solar Cell Optimization and Testingmentioning
confidence: 82%
“…Unlike nanoparticle based ZnO, sol-gel synthesis requires annealing process at higher temperature to remove organic components and crystalline. [ 75,76 ] Thus, nanoparticle solution is more suitable for the devices that need low temperature process and fl exibility.…”
Section: Metal Oxide (Tio 2 Zno)mentioning
confidence: 99%